Low-anisotropy easily-welded LCP (Liquid Crystal Polymer) resin and preparation method thereof
By introducing side chains and disulfide bond structures into LCP resin, the problems of poor welding mark strength and anisotropy are solved, better mechanical properties and self-repair functions are achieved, and the service life of the material is extended.
Patent Information
- Application Number
- CN202411600499.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-07
AI Technical Summary
The existing LCP resins have poor welding mark strength and anisotropy problems during welding, which affect their mechanical properties and service life.
Through molecular structure design, rigid monomers with side chains are synthesized, and liquid crystal polymer resins with side chains containing disulfide bonds are prepared by melt polymerization to improve their weld mark strength and anisotropy.
It significantly improves the welding mark strength and anisotropy of LCP resin, enhances its mechanical properties, and imparts a self-healing function, extends the service life of the material.
Smart Images

Figure CN119390962A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, in particular to a low anisotropic fusible LCP resin and a preparation method thereof. Background Art
[0002] Liquid crystal polymer (LCP) is a polymer material composed of rigid molecular chains that can exist in a liquid crystal phase under certain physical conditions. It is characterized by a high molecular weight and an orderly orientation. When LCP exists in a liquid crystal phase, it has a low viscosity and is highly oriented. After being cooled and solidified, its morphology can be stably maintained. Therefore, LCP materials have excellent mechanical properties. In addition, LCP materials also have good heat resistance, low moisture absorption, chemical corrosion resistance, weather resistance, flame retardancy, low dielectric constant and dielectric loss factor, etc., and are widely used in electronic and electrical components such as printed circuit boards, semiconductors, connectors, relays and switches.
[0003] LCP material also has excellent processing fluidity and fast curing speed, and is suitable for processing by injection molding. Compared with polyphenylene sulfide (PPS) and high temperature resistant nylon (HT-PA), LCP parts have advantages such as no flash. However, since the LCP molecular chain is in the shape of a rigid rod, it is easy to orient along the molecular chain in the flow direction, resulting in a large difference in the performance of the molded parts parallel to the flow direction and perpendicular to the flow direction, as well as the existence of disadvantages such as poor weld mark strength. In recent years, the defects of poor weld mark strength and anisotropy of LCP materials have been improved to a certain extent through methods such as mold design, but there are fewer studies on improving the poor weld mark strength and anisotropy of LCP materials from the perspective of molecular structure design. Summary of the invention
[0004] In view of the deficiencies in the prior art, the object of the present invention is to provide a low anisotropic, easily fusible LCP resin and a preparation method thereof. Through molecular structure design, a rigid monomer with a side chain is first synthesized, and then a liquid crystal polymer resin containing a disulfide bond in the side chain is prepared by melt polymerization, which can effectively solve the technical problems of poor weld mark strength and anisotropy of the LCP resin.
[0005] In order to achieve the above technical objectives, the present invention adopts the following technical solutions: A technical solution of the present invention provides a low anisotropic fusible LCP resin having a molecular structure as shown in Formula I:
[0006] Formula I In formula I, R1 is a saturated alkane chain; R2 is a naphthalene ring structure, and n is any integer between 50 and 100.
[0007] In some possible embodiments, in the molecular structure of the LCP resin, formula I: The general structural formula of R1 is C n H 2n , n=1~5; R2 has any one of the following structural formulas:
[0008] The present invention also provides a method for preparing the low anisotropic fusible LCP resin in the above scheme, comprising the following steps: S1. Preparation of rigid monomers linked by flexible small molecules: Add the flexible chain small molecule monomer and 5-hydroxyisophthalic acid into a reaction kettle, mix them evenly, add the first esterification catalyst, heat and stir, evacuate during the reaction, and after the reaction is completed, cool to room temperature to obtain a rigid monomer linked by a flexible small molecule; S2. Preparation of liquid crystal polymer with network structure: Add the rigid monomer linked by the flexible small molecules obtained in step S1 into a temperature and pressure resistant reactor, then add the rigid monomer with a naphthalene ring, pass nitrogen to deoxygenate, mix evenly, add the second esterification catalyst, heat and stir, evacuate during the reaction, and after the reaction is completed, cool to room temperature to obtain a liquid crystal polymer with a network structure.
[0009] In some possible embodiments, in step S1, the rigid monomer linked by the flexible small molecule has a molecular structure as shown in Formula V:
[0010] Formula V In formula V, R1 is a saturated alkane chain, and its structural formula is C n H 2n , n=1~5; In some possible embodiments, in step S1, the flexible chain small molecule monomer has a disulfide bond and two terminal carboxyl groups.
[0011] In some possible implementations, in step S1, the flexible chain small molecule monomer is 3,3'-dithiodipropionic acid or 4,4'-dithiodibutyric acid.
[0012] In some possible implementations, in step S1, the first esterification catalyst is a solid acid catalyst.
[0013] Furthermore, in step S1, the first esterification catalyst is any one of p-toluenesulfonic acid, zirconium sulfate, and tin sulfate.
[0014] In some possible implementations, in step S1, the molar mass ratio of the flexible chain small molecule monomer to 5-hydroxyisophthalic acid is 1:(2-2.2); the mass of the first esterification catalyst accounts for 0.02-0.05% of the mass of 5-hydroxyisophthalic acid.
[0015] Exemplarily, the molar mass ratio of the flexible chain small molecule monomer to 5-hydroxyisophthalic acid is 1:2, 1:2.1 or 1:2.2; the mass of the first esterification catalyst accounts for 0.02%, 0.03%, 0.04% or 0.05% of the mass of 5-hydroxyisophthalic acid.
[0016] In some possible implementations, in step S2, the rigid monomer with a naphthalene ring is any one of 1,5-dihydroxynaphthalene, 2,6-dihydroxynaphthalene and 2,7-dihydroxynaphthalene.
[0017] In some possible implementations, in step S2, the second esterification catalyst is an acetate catalyst.
[0018] Furthermore, in step S2, the second esterification catalyst is any one of calcium acetate, magnesium acetate and zinc acetate.
[0019] In some possible implementations, in step S2, the molar mass ratio of the rigid monomer linked by the flexible small molecule to the rigid monomer with a naphthalene ring is 1:(2-2.5); the mass of the second esterification catalyst is 0.005-0.01% of the mass of the rigid monomer with a naphthalene ring.
[0020] Exemplarily, the molar mass ratio of the rigid monomer linked by flexible small molecules to the rigid monomer with a naphthalene ring is 1:2, 1:2.1, 1:2.2, 1:2.3, 1:2.4 or 1:2.5; the mass of the second esterification catalyst is 0.005%, 0.006%, 0.007%, 0.008%, 0.009% or 0.01% of the mass of the rigid monomer with a naphthalene ring.
[0021] In some possible implementations, in step S1, the stirring speed is 400-600 r / min, the reaction temperature is 120-140° C., and the reaction time is 1-2 h; Exemplarily, in step S1, the stirring speed is 400 r / min, 500 r / min or 600 r / min, the reaction temperature is 120, 130 or 140° C., and the reaction time is 1 h, 1.5 h or 2 h.
[0022] In step S2, the stirring speed is 400-600 r / min, the reaction temperature is 200-250° C., and the reaction time is 1-2 h.
[0023] In step S2, the stirring speed is 400, 500 or 600 r / min, the reaction temperature is 200°C, 210°C, 220°C, 230°C, 240°C or 250°C, and the reaction time is 1 h, 1.5 h or 2 h.
[0024] The present invention has the following beneficial effects: 1. The present invention introduces a flexible chain small molecule structure in advance between LCP rigid monomers through molecular structure design, and then synthesizes a network structure LCP resin through melt copolymerization. Due to the introduction of flexible chain small molecules, the problems of anisotropy and poor weld mark strength of LCP resin can be significantly improved.
[0025] 2. The present invention introduces dynamic covalent disulfide bonds on the flexible molecular chain of LCP resin. During the melt welding process of LCP resin, the dynamic disulfide bonds on the contact surfaces of the two welding bodies can form new covalent bonds by mutual attraction, thereby significantly enhancing the mechanical strength of the welding position. At the same time, the introduction of dynamic covalent disulfide bonds enables LCP resin to have a self-repairing function. The material can automatically detect and repair microscopic damage, such as small cracks, thereby effectively preventing the further expansion of the damage and significantly extending the service life of the LCP material. DETAILED DESCRIPTION
[0026] The following specific embodiments illustrate the implementation of the present invention, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Although the description of the present invention will be introduced in conjunction with the preferred embodiment, it does not mean that the features of this invention are limited to the implementation.
[0027] In an embodiment of the present invention, a low anisotropic fusible LCP resin is provided, which has a molecular structure as shown in Formula I:
[0028] Formula I In Formula I, the degree of polymerization n is any integer between 50 and 100; the general structural formula of R1 is C n H 2n , n=1~5; R2 is a naphthalene ring structure having any one of the following structural formulas Ⅱ~Ⅳ:
[0029] The embodiment of the present invention also provides a method for preparing the above-mentioned low anisotropy fusible LCP resin, comprising the following steps: S1. Preparation of rigid monomers linked by flexible small molecules: Add the flexible chain small molecule monomer and 5-hydroxyisophthalic acid into a reaction kettle, mix them evenly, add the first esterification catalyst, heat and stir, evacuate during the reaction, and after the reaction is completed, cool to room temperature to obtain a rigid monomer linked by a flexible small molecule; S2. Preparation of liquid crystal polymer with network structure: Add the rigid monomer linked by the flexible small molecules obtained in step S1 into a temperature and pressure resistant reactor, then add the rigid monomer with a naphthalene ring, pass nitrogen to deoxygenate, mix evenly, add the second esterification catalyst, heat and stir, evacuate during the reaction, and after the reaction is completed, cool to room temperature to obtain a liquid crystal polymer with a network structure.
[0030] In some embodiments, the method for preparing the low anisotropic fusible LCP resin comprises the following steps: S1. Preparation of rigid monomers linked by flexible small molecules: Add the flexible chain small molecule monomer and 5-hydroxyisophthalic acid into a reactor, mix them evenly, add the first esterification catalyst, stir at 120-140°C at a speed of 400-600r / min for 1-2h, evacuate the system during the reaction to extract the water vapor in the reaction system to promote the reaction in the direction of esterification, and after the reaction is completed, cool to room temperature to obtain a rigid monomer linked by a flexible small molecule; wherein the molar mass ratio of the flexible chain small molecule monomer to 5-hydroxyisophthalic acid is 1:(2-2.2), and the amount of the first esterification catalyst is 0.02-0.05% of the mass of 5-hydroxyisophthalic acid.
[0031] S2. Preparation of liquid crystal polymer with network structure: Add the rigid monomer linked by flexible small molecules obtained in step S1 to a temperature and pressure resistant reactor, then add the rigid monomer with naphthalene ring, pass nitrogen to deoxygenate, mix evenly, add the second esterification catalyst, stir at 200-250°C at a speed of 400-600r / min for 1-2h, and evacuate during the reaction; after the reaction is completed, cool to room temperature to obtain a liquid crystal polymer with a network structure, and grind to obtain LCP resin powder. Among them, the molar mass ratio of the rigid monomer linked by flexible small molecules to the rigid monomer with naphthalene ring is 1: (2-2.5), and the amount of the second esterification catalyst is 0.005-0.01% of the mass of the rigid monomer with naphthalene ring.
[0032] In some embodiments, in the above step S1, the rigid monomer linked by the flexible small molecule has a molecular structure as shown in Formula V:
[0033] Formula V In formula V, R1 is a saturated alkane chain, and its structural formula is C n H2n , n=1~5, for example, the structural formula of R1 is C2H4 or C3H6.
[0034] In some embodiments, in step S1, the flexible chain small molecule monomer has a disulfide bond and two terminal carboxyl groups.
[0035] In some embodiments, in step S1, the flexible chain small molecule monomer is 3,3'-dithiodipropionic acid or 4,4'-dithiodibutyric acid. The first esterification catalyst is a solid acid catalyst, which is any one of p-toluenesulfonic acid, zirconium sulfate, and tin sulfate.
[0036] In some embodiments, in step S2, the rigid monomer with a naphthalene ring is any one of 1,5-dihydroxynaphthalene, 2,6-dihydroxynaphthalene and 2,7-dihydroxynaphthalene. The second esterification catalyst is an acetate catalyst, which can be any one of calcium acetate, magnesium acetate and zinc acetate.
[0037] To make the purpose, technical scheme and advantages of the present invention clearer, the embodiments of the present invention will be described in further detail below. In the following examples, unless otherwise specified, the raw materials used are common commercial products and the reagents are analytically pure reagents.
[0038] Example 1 This embodiment provides a low anisotropic fusible LCP resin, and its molecular structure is as follows:
[0039] This embodiment also provides a method for preparing the above-mentioned low anisotropy fusible LCP resin, comprising the following steps: S1. Preparation of rigid monomers linked by flexible small molecules: 210.27g (1mol) 3,3'-dithiodipropionic acid and 364.26g (2mol) 5-hydroxyisophthalic acid were added to the reactor, stirred at 400r / min for 30min, then 0.073g p-toluenesulfonic acid as an esterification catalyst was added, stirred at 400r / min for 1h at 120°C, vacuumed during the reaction, and after the reaction was completed, cooled to room temperature to obtain a rigid monomer linked by a flexible small molecule. According to calculations, the molar ratio of 3,3'-dithiodipropionic acid to 5-hydroxyisophthalic acid was 1:2, and p-toluenesulfonic acid accounted for 0.02% of the mass of 5-hydroxyisophthalic acid.
[0040] S2. Preparation of liquid crystal polymer with network structure: 540g (1 mol) of the rigid monomer linked by the flexible small molecule obtained in step S1 was added to a temperature and pressure resistant reactor, and then 320.34g (2 mol) of 1,5-dihydroxynaphthalene was added, nitrogen was passed to deoxygenate, and stirred at a speed of 400r / min for 30min, and then 0.016g of calcium acetate, an esterification catalyst, was added, and stirred at a speed of 400r / min at 200°C for 1h. Vacuum was drawn during the reaction. After the reaction was completed, it was cooled to room temperature to obtain a liquid crystal polymer with a network structure, and LCP resin powder was obtained by crushing. According to calculation, the molar mass ratio of the rigid monomer linked by the flexible small molecule to the rigid monomer with a naphthalene ring is 1:2, and the amount of the second esterification catalyst is 0.005% of the mass of the rigid monomer with a naphthalene ring.
[0041] Example 2 This embodiment provides a low anisotropic fusible LCP resin, and its molecular structure is as follows:
[0042] This embodiment also provides a method for preparing the above-mentioned low anisotropy fusible LCP resin, comprising the following steps: S1. Preparation of rigid monomers linked by flexible small molecules: 238.32g (1mol) of 4,4'-dithiodibutyric acid and 382.47g (2.1mol) of 5-hydroxyisophthalic acid were added to the reactor, stirred at 500r / min for 40min, then 0.115g of zirconium sulfate, an esterification catalyst, was added, stirred at 130°C at 500r / min for 2h, vacuumed during the reaction, and after the reaction was completed, cooled to room temperature to obtain a rigid monomer linked by a flexible small molecule. According to calculations, the molar ratio of 4,4'-dithiodibutyric acid to 5-hydroxyisophthalic acid was 1:2.1, and zirconium sulfate accounted for 0.03% of the mass of 5-hydroxyisophthalic acid.
[0043] S2. Preparation of liquid crystal polymer with network structure: 580g (1mol) of the rigid monomer linked by the flexible small molecule obtained in step S1 was added to a temperature and pressure resistant reactor, and then 368.39g (2.3mol) of 2,6-dihydroxynaphthalene was added, nitrogen was passed to deoxygenate, and stirred at a speed of 500r / min for 50min, and then 0.029g of esterification catalyst magnesium acetate was added, and stirred at a speed of 500r / min at 220°C for 2h, and vacuum was drawn during the reaction. After the reaction was completed, it was cooled to room temperature to obtain a liquid crystal polymer with a network structure, and LCP resin powder was obtained by crushing. According to calculation, the molar mass ratio of the rigid monomer linked by the flexible small molecule to the rigid monomer with a naphthalene ring is 1:2.3, and the amount of the second esterification catalyst is 0.008% of the mass of the rigid monomer with a naphthalene ring.
[0044] Example 3 This embodiment provides a low anisotropic fusible LCP resin, and its molecular structure is as follows:
[0045] This embodiment also provides a method for preparing the above-mentioned low anisotropy fusible LCP resin, comprising the following steps: S1. Preparation of rigid monomers linked by flexible small molecules: 238.32g (1mol) of 4,4'-dithiodibutyric acid and 400.68g (2.2mol) of 5-hydroxyisophthalic acid were added to the reactor, stirred at 600r / min for 60min, then 0.2g of esterification catalyst tin sulfate was added, stirred at 140℃ at 600r / min for 2h, vacuum was drawn during the reaction, water vapor in the system was drawn out, and the reaction was promoted to the esterification direction. After the reaction was completed, it was cooled to room temperature to obtain a rigid monomer linked by a flexible small molecule. It was calculated that the molar ratio of 4,4'-dithiodibutyric acid to 5-hydroxyisophthalic acid was 1:2.2, and tin sulfate accounted for 0.05% of the mass of 5-hydroxyisophthalic acid.
[0046] S2. Preparation of liquid crystal polymer with network structure: 630g (1 mol) of the rigid monomer linked by the flexible small molecule obtained in step S1 was added to a temperature and pressure resistant reactor, and then 400.42g (2.5 mol) of 2,7-dihydroxynaphthalene was added, nitrogen was passed to deoxygenate, and stirred at a speed of 600r / min for 60min, and then 0.04g of esterification catalyst zinc acetate was added, and stirred at a speed of 600r / min at 250°C for 2h, and vacuum was drawn during the reaction. After the reaction was completed, it was cooled to room temperature to obtain a liquid crystal polymer with a network structure, and LCP resin powder was obtained by crushing. According to calculation, the molar mass ratio of the rigid monomer linked by the flexible small molecule to the rigid monomer with a naphthalene ring is 1:2.5, and the amount of the second esterification catalyst is 0.01% of the mass of the rigid monomer with a naphthalene ring.
[0047] Comparative Example 1 This comparative example provides a LCP resin, and its molecular structure is as follows:
[0048] The preparation method of the above LCP resin comprises the following steps: 364.26 g of 5-hydroxyisophthalic acid was added into a heat-resistant and pressure-resistant reactor, and then 320.34 g of 1,5-dihydroxynaphthalene was added, nitrogen was passed to deoxygenate, and the mixture was stirred at a speed of 400 r / min for 30 min. Subsequently, 0.016 g of calcium acetate, an esterification catalyst, was added, and the mixture was stirred at a speed of 400 r / min at 200°C for 1 h. Vacuum was applied during the reaction. After the reaction was completed, the mixture was cooled to room temperature to obtain a liquid crystal polymer with a network structure, which was then pulverized to obtain an LCP resin powder.
[0049] Performance Test: The LCP resins prepared in Examples 1 to 3 and Comparative Example 1 were tested for performance respectively: Use a universal mechanical testing machine (electronic universal testing machine CMT6103) to test mechanical properties. The test method refers to the standard ASTM D638 standard test method for tensile properties of plastics; Prepare a weld mark strength test specimen according to the specimen used to test the tensile strength in the direction perpendicular to the molecular orientation, cut the specimen in the middle, and then form a new test specimen through welding and fusion solidification, and use a universal mechanical testing machine to test the tensile strength of the weld mark; The melting point of the resins was measured using a Mettler Toledo differential scanning calorimeter (DSC).
[0050] The test results are shown in Table 1 below: Table 1 LCP resin properties of Examples 1 to 3 and Comparative Example 1
[0051] Analyzing the data in Table 1, it can be seen from the test results of Examples 1 to 3 and Comparative Example 1 that the introduction of flexible chain small molecule groups can significantly improve the anisotropy of liquid crystal polymers, and the mechanical properties of LCP resins in the direction perpendicular to the molecular orientation are significantly enhanced, while the mechanical properties in the direction of molecular orientation are not significantly reduced. In addition, the introduction of flexible chain small molecules reduces the melting point of the resin and broadens the practical application range of the resin.
[0052] In Examples 1 to 3, after the splines are cut, during the welding fusion and curing process, the dynamic disulfide bonds on the contact surfaces of the two welded bodies can form new covalent bonds by mutual attraction, and have a certain self-repair function. The cut surface is relatively smooth after curing, and the mechanical properties of the splines are not significantly reduced. After welding, the splines of Example 1 have obvious welding marks and the mechanical properties are significantly reduced.
[0053] By comparing Example 1 and Example 2, it can be seen that the longer the flexible molecular chain contained in the LCP resin, the more obvious the reduction in the melting point of the resin, which is more conducive to lowering the processing temperature and improving the resin fluidity. At the same time, the length of the flexible molecular chain has no significant effect on the mechanical properties in the direction of molecular orientation, but has a greater effect on the mechanical properties in the direction perpendicular to the molecular orientation. The shorter the flexible molecular chain, the stronger the interaction.
[0054] It can be seen from the comparison of Example 2 and Example 3 that when the length of the flexible molecular chain in the LCP resin is consistent, the resin melting point is not significantly reduced, which is mainly affected by the rigid monomer of the naphthalene ring in the molecular structure. The farther the two phenolic hydroxyl groups on the naphthalene ring are spaced, the better the melting point and mechanical properties of the synthetic resin.
[0055] By comparing Example 1 with Comparative Example 1, it can be seen that the flexible chain small molecule structure is not introduced in Comparative Example 1. Although the mechanical properties of the obtained LCP resin in the molecular orientation direction are relatively excellent, the mechanical properties in the direction perpendicular to the molecular orientation are relatively poor, and the melting point is relatively high.
[0056] It can be seen that the present invention can effectively improve the mechanical strength in the direction perpendicular to the molecular orientation and reduce the melting point of the resin while ensuring the mechanical properties in the molecular orientation direction of the LCP resin. The disulfide bonds in its structure can give the resin self-healing ability, further improving the application prospects and service life of the resin.
[0057] Although the preferred embodiments of the present invention have been disclosed as above, they are not intended to limit the present invention. Any person skilled in the art may make possible changes and modifications to the technical solutions of the present invention by using the methods and technical contents disclosed above without departing from the spirit and scope of the present invention. Therefore, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the contents of the technical solutions of the present invention shall fall within the protection scope of the technical solutions of the present invention.
Claims
1. A low anisotropic, easily fusible LCP resin, characterized in that: It has a molecular structure as shown in Formula I: Formula I In formula I, R1 is a saturated alkane chain; R2 is a naphthalene ring structure, and n is any integer between 50 and 100.
2. The low anisotropic fusible LCP resin according to claim 1, characterized in that: In the molecular structure formula I of the LCP resin: The general structural formula of R1 is C n H 2n , n=1~5; R2 has any one of the structural formulas shown in the following formulas II to IV:
3. A method for preparing a low anisotropic fusible LCP resin as claimed in claim 1 or 2, characterized in that: The steps include: S1. Preparation of rigid monomers linked by flexible small molecules: Adding a flexible chain small molecule monomer and 5-hydroxyisophthalic acid into a reaction kettle, mixing them evenly, adding a first esterification catalyst, heating and stirring, vacuuming during the reaction, and cooling to room temperature after the reaction is completed to obtain a rigid monomer linked by a flexible small molecule; the flexible chain small molecule monomer has a disulfide bond and two terminal carboxyl groups; S2. Preparation of liquid crystal polymer with network structure: Add the rigid monomer linked by the flexible small molecules obtained in step S1 into a temperature and pressure resistant reactor, then add the rigid monomer with a naphthalene ring, pass nitrogen to deoxygenate, mix evenly, add the second esterification catalyst, heat and stir, evacuate during the reaction, and after the reaction is completed, cool to room temperature to obtain a liquid crystal polymer with a network structure.
4. The preparation method according to claim 3, characterized in that: In step S1, the rigid monomer linked by the flexible small molecule has a molecular structure as shown in Formula V: Formula V In formula V, R1 is a saturated alkane chain, and the general structural formula is C n H 2n , n=1~5.
5. The preparation method according to claim 3, characterized in that: In step S1, the flexible chain small molecule monomer is 3,3'-dithiodipropionic acid or 4,4'-dithiodibutyric acid.
6. The preparation method according to claim 3, characterized in that: In step S2, the rigid monomer having a naphthalene ring is any one of 1,5-dihydroxynaphthalene, 2,6-dihydroxynaphthalene and 2,7-dihydroxynaphthalene.
7. The preparation method according to claim 3, characterized in that: In step S1, the first esterification catalyst is a solid acid catalyst; in step S2, the second esterification catalyst is an acetate catalyst.
8. The preparation method according to claim 3, characterized in that: In step S1, the molar mass ratio of the flexible chain small molecule monomer to 5-hydroxyisophthalic acid is 1:(2-2.2); the mass of the first esterification catalyst accounts for 0.02-0.05% of the mass of 5-hydroxyisophthalic acid.
9. The preparation method according to claim 3, characterized in that: In step S2, the molar mass ratio of the rigid monomer linked by the flexible small molecule to the rigid monomer with a naphthalene ring is 1:(2-2.5); the mass of the second esterification catalyst is 0.005-0.01% of the mass of the rigid monomer with a naphthalene ring.
10. The preparation method according to claim 3, characterized in that: In step S1, the stirring speed is 400-600 r / min, the reaction temperature is 120-140° C., and the reaction time is 1-2 h; In step S2, the stirring speed is 400-600 r / min, the reaction temperature is 200-250° C., and the reaction time is 1-2 h.